Railway and ports organization in the Republic of South Africa and Turkey: The integrator's paradise? - Louis S. Thompson (Organisation for Economic Co-operation and Development (OECD), Joint Transport Research Centre (JTRC), 2009)
This paper looks in detail at the cases of two countries that exhibit extreme cases of transport organization. In both countries, the railway and most of the ports are under unitary control, with essentially no regulation and only limited information available to assess behavior. If economies of scale are important, if the integration achieved by organizational unification is truly beneficial, and if competition is not needed to limit the behavior of the unified organizations, then these countries should be at the cutting edge of system performance, with high efficiency, low costs and excellent service. If the reverse is true, then they furnish at least a few data points for the analysis of the importance of diversity of organization and competition within the system.
Keywords: 330